The Islamic state and the Anglican communion - TSE, Justin Kh (Institutional Knowledge at Singapore Management University, 2014)
When Canon Andrew White, popularly known as the ‘Vicar of Baghdad,’ reported that Islamic State had cut a five-year-old child he baptized in half, the Church of England got behind the #WeAreN Twitter hashtag and Facebook profile picture campaign. The Archbishop of Canterbury, Justin Welby, has changed his Facebook page’s picture to the Arabic letter ‘N’ in solidarity with Christians whose Mosul homes were marked with the letter in orders to either convert to IS’s version of Islam or face the sword. I want to argue that whatever one might believe about the incoherence of Anglican theology, the Vicar of Baghdad and the Archbishop of Canterbury resist the Islamic State through a coherent Anglican political theology. I want to argue, moreover, that that vision can be found in the Venerable Bede’s Ecclesiastical History of the English People.